Comparison of Metaheuristic Optimization Algorithms for Quadrotor PID Controllers - Batikan Erdem Demir; Funda Demir (Tehnički Vjesnik, 2023)
In the present study, different solution methods are discussed in order to control the quadrotor with the most optimal PID parameters for the determined purposes. One of these methods is to make use of meta-heuristic algorithms in control systems. There are some limitations of using a PID controller as a classical construct. However, it is thought that more successful results will be obtained by optimizing its parameters through meta-heuristic algorithms. Initially, the mathematical model of the vehicle was created in MATLAB/Simulink. Then, genetic algorithms (GA), artificial bee colony (ABC), particle swarm optimization (PSO) and firefly algorithms (FA) were determined respectively as optimization methods. And these optimization methods used to determine the PID control parameters are applied to the developed mathematical model in the MATLAB/Simulink environment. In addition, the performances of the optimization methods are evaluated according to the comparison criteria. As a result of the comparison carried out according to ITAE (Integral Time Absolute Error) fitness criteria, ABC (1.2% - 4.4%) in terms of altitude, FA (4% - 13%) in terms of roll angle, GA (13% - %21) in terms of pitch angle, and PSO (4% - %15) in terms of yaw angle has been more successful than other methods.